Bibliometric Analysis: Collaboration Networks In Discovery Learning Research - Andi Suparjo; Edwin Musdi; Yerizon Yerizon; I Made Arnawa (Postgraduate, University of Mataram, 2024)
This research identifies publications related to Discovery learning. Discovery learning is a learning model that encourages active learning in students through self-discovery and research so that the results achieved are long-lasting and difficult to forget. This research aims to identify and analyze articles researching Discovery Learning that have been published in several reputable international journals published in the 2014-2023 period, which was carried out using bibliometric studies. Bibliometric analysis produced four findings: publications about Discovery Learning in Scopus-indexed journals have been in a fluid and balanced pattern every year for the last ten years; 328 of the ten journals producing the most articles have been published. The top-ranked journal published 15 articles, and the tenth-ranked journal published five articles; The most citations occurred in articles published in 2020 with a total of 1101 citations. The most cited article was written by B.R. Goldsmith with 241 citations; The author's keywords that are most frequently used in the top three are discovery, machine, and machine learning